THE COMPARATION OF MAQᾹṢῙD IMPLIMENTATION'S IBN ‘AṢŪR AND MUNᾹWIR SJADZALI'S IN QS. 4: 11 - Shofa, Ida Kurnia (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
This paper will discuss the discourse of inheritance in QS. 4: 11 according to modern figure, Ibn â€˜Aá¹£Å«r and Munawar Sjadzali. So, the purpose of this reseach is to express base of maqÄá¹£Ä«d application that used by them. This research is library research with diskriptive-analysis and comparation method. The result of this research is that two figures found a significant values in that surah with different maqashid concept. Ibnu â€˜Aá¹£Å«r understood the surah (QS. 4: 11) is as an awarding attention for muslem women in the discourse of inheritance that they get a half of a man proportion. Even before the revelation of that surah, the women's right were not given. While, Munawir Sjadzali understood that surah by searching an ideal value and contextualize whit the situation and condition in his country with formulation 1:1 for man and women which considered the roles and positions woman are relatively same with a man along the demands of the times.